2013
DOI: 10.5573/jsts.2013.13.6.647
|View full text |Cite
|
Sign up to set email alerts
|

A Study of SCEs and Analog FOMs in GS-DG-MOSFET with Lateral Asymmetric Channel Doping

Abstract: Abstract-The design and analysis of analog circuit application on CMOS technology are a challenge in deep sub-micrometer process. This paper is a study on the performance value of Double Gate (DG) Metal Oxide Semiconductor Field Effect Transistor (MOSFET) with Gate Stack and the channel engineering Single Halo (SH), Double Halo (DH). Four different structures have been analysed keeping channel length constant. The short channel parameters and different sub-threshold analog figures of merit (FOMs) are analysed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…9 Similarly, the impact of gate metal work function on various performances of GS-DG MOS-FET has been reported. 10 Sahu et al, 11 have demonstrated extensively about the effect of halo implanted doping profile, i.e., single halo (SH) and double halo (DH) in DG MOSFET. Finally in Pradhan et al, 12 a novel device design i.e., triple material (TM) gate metal with halo implanted doping profile (SH and DH) has been introduced and various dc performances have been closely analyzed.…”
mentioning
confidence: 99%
“…9 Similarly, the impact of gate metal work function on various performances of GS-DG MOS-FET has been reported. 10 Sahu et al, 11 have demonstrated extensively about the effect of halo implanted doping profile, i.e., single halo (SH) and double halo (DH) in DG MOSFET. Finally in Pradhan et al, 12 a novel device design i.e., triple material (TM) gate metal with halo implanted doping profile (SH and DH) has been introduced and various dc performances have been closely analyzed.…”
mentioning
confidence: 99%
“…The multi-gate structures like Double Gate (DG) MOSFET fabricated on SOI wafers is one of the most promising candidates due to its attractive features of low leakage current, high current drivability (I on ), transconductance (g m ), reduced short channel effects (SCEs), steeper subthreshold slopes, and suppression of latch-up phenomenon [26]- [31]. In a recent work [32]- [34], a detailed analysis of inflection point to examine its reliability issues over a wide range of temperature variations (100 K-400 K) for both analog and RF applications of DG MOSFET with HKMG technology was reported.…”
Section: Significance Of Ztc Biasmentioning
confidence: 99%
“…As channel length scaling of the conventional metaloxide-semiconductor field-effect transistors (MOSFETs) continues, they encounter several issues closely related with short-channel effects (SCEs) [1][2][3][4]. In the shortchannel MOSFETs, the presence of back-to-back two p-n junctions becomes more prominent as a weakness.…”
Section: Introductionmentioning
confidence: 99%